2014
DOI: 10.1021/jo500787q
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Electrogenerated Intermediates in Nitro-Substituted Nor-β-lapachones: The Structure of Radical Species during Successive Electron Transfer in Multiredox Centers

Abstract: Electrochemical, spectroelectrochemical, and theoretical studies of the reduction reactions in nor-β-lapachone derivatives including a nitro redox center showed that reduction of the compounds involves the formation of several radical intermediates, including a biradical dianion resultant from the separate reduction of the quinone and nitro groups in the molecules. Theoretical descriptions of the corresponding Fukui functions f(αα)⁺ and f(ββ)⁺(r) and LUMO densities considering finite differences and frozen cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…This strategy has previously led to consistent values and to predict site reactive effects in agreement with experiments. [35][36][37] Only selected values associated to the urea moieties were used because, as mentioned above, this region is the reactive site for the binding process ( The results showed that the highest value correspond to the ∑ ߱ ା ሺሻ for the fragment containing the phenyl residue (10), which suggests that this site is the more prone for charge acceptance during the hydrogen bonding process, compared to the other ureas. Furthermore, the calculated data for this residue is significantly different from those for compounds 7-9, opposite to the previously described behavior of the global criteria ω + ( Table 3).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has previously led to consistent values and to predict site reactive effects in agreement with experiments. [35][36][37] Only selected values associated to the urea moieties were used because, as mentioned above, this region is the reactive site for the binding process ( The results showed that the highest value correspond to the ∑ ߱ ା ሺሻ for the fragment containing the phenyl residue (10), which suggests that this site is the more prone for charge acceptance during the hydrogen bonding process, compared to the other ureas. Furthermore, the calculated data for this residue is significantly different from those for compounds 7-9, opposite to the previously described behavior of the global criteria ω + ( Table 3).…”
Section: Introductionmentioning
confidence: 99%
“…[20] For explaining the biological activities of nor-β-lapachone derivatives, Frontana and co-workers have studied the various redox states of this molecule by experimental and theoretical studies. [21] The CV of this compound shows the four single electron reduction waves with the E 1/2 value of À 1.20 V, À 1.61 V, À 1.73 V and À 2.45 V vs Fc/Fc + with first three being reversible and the last cathodic wave being irreversible. The first electron reduces the quinone moiety to form the quinone radical anion, while the second electron reduction involves the formation of biradical dianion state, in which both unpaired electrons are located on the quinone and the nitro group.…”
Section: Organic Multi-electron Acceptorsmentioning
confidence: 88%
“…The latter is usually protonated by residual water to the respective C−H bond. 13 As the electrophilic character of quinones has been proved to be relevant for several biological activities, 2 and considering that the presence of a nitro substituent certainly makes the electron capture by the quinone moiety easier, 12 this paper intends to consider the mutual influence of the redox groups on the electron transfer processes of the present pterocarpanquinones ( Figure 1) and the structural properties of their electrochemically generated radical anions. The presence of halogens also contribute to the activity and to the electrochemical profile.…”
Section: Introductionmentioning
confidence: 99%